2018
DOI: 10.1002/jsfa.9380
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biochar and compost amendment on soil quality, growth and yield of a replanted apple orchard in a 4‐year field study

Abstract: BACKGROUND Numerous studies have addressed the positive effects of organic amendments on soil and plant productivity under short‐term field studies. However, to date, few studies have been conducted on the effects of organic amendment on the orchards where high nutrient bioavailability is required. This study deals with the effects of biochar and compost on soil quality, growth and yield of a replanted apple orchard in the northeast of Iran. RESULTS Biochar+compost application resulted in 37% and 300% higher s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 31 publications
5
13
1
Order By: Relevance
“…According to Prasad et al [35], biochar can contain high amounts of available Mn and P, which are readily released to the soil. The results corroborate the study by Safaei Khorram et al [36], who reported that the application of biochar increased the availability of K and P, benefitting plant growth. It is also possible that biochar reduces the availability of elements that are already low in the soil, such as Mg and Cu [37,38].…”
Section: Effects Of Açaí Biochar and Compost On The Properties Of Fe Mining Soilsupporting
confidence: 91%
See 1 more Smart Citation
“…According to Prasad et al [35], biochar can contain high amounts of available Mn and P, which are readily released to the soil. The results corroborate the study by Safaei Khorram et al [36], who reported that the application of biochar increased the availability of K and P, benefitting plant growth. It is also possible that biochar reduces the availability of elements that are already low in the soil, such as Mg and Cu [37,38].…”
Section: Effects Of Açaí Biochar and Compost On The Properties Of Fe Mining Soilsupporting
confidence: 91%
“…Compost increased the SB, K, Ca, B, and OM contents while it decreased Mn and Zn availability. Similarly, biochar increased P and K availability and soil pH while it decreased Mg, Cu, and Zn availability, a finding also observed by Mensah and Frimpong [29] and Safaei Khorram et al [36].…”
Section: Effects Of Açaí Biochar and Compost On The Properties Of Fe Mining Soilsupporting
confidence: 79%
“…Dry matter content of Chinese cabbage plants was high, 9-11%, but comparable to the figures reported by Kosson et al [47]. The variability observed reflects a combination of abiotic factors (climate) and the soil system [48][49][50][51]. Based on previous research it would be interesting to focus further research on changes in the soil that might occur when using OF for a longer period (several years).…”
Section: Discussionsupporting
confidence: 81%
“…Based on previous research it would be interesting to focus further research on changes in the soil that might occur when using OF for a longer period (several years). It would be interesting to explore how the nutritive value of OF changes with an altered collection of raw F. Japonica material for its preparation (different time of year) [48][49][50]52].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of biochar combined with compost can be performed in two ways: one is that biochar is mixed with compost after the composting process is finished, and the other is that biochar is added to compost at the early stage of the composting process [222]. The first method was reported as enhancing soil nutrient content and crops productivity [89,223], while other authors showed that biochar-based compost is more beneficial for soil and plants. Glaba et al [224] found that the application of biocharbased compost improves the water retention capacity of sandy soils to a greater extent than compost without biochar.…”
Section: Biochar In Compostingmentioning
confidence: 99%